2002
DOI: 10.1583/1545-1550(2002)009<0786:iocpdo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cerebral Protection Devices on Early Outcome of Carotid Stenting

Abstract: Our data suggest that percutaneous dilation and stenting of the carotid arteries protected by cerebral protection devices is feasible and effective. In a consecutive series, the use of the cerebral protection systems reduced the acute neurological event rate related to embolic complications by 79%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 14 publications
1
32
0
2
Order By: Relevance
“…1,[17][18][19] Because of this relatively high incidence of adverse effects, efforts have been made to reduce their incidence by using CPDs during CAS. 4,5,20,21 An extensive literature review indicates that the use of CPD can decrease the incidence of 30-day combined stroke and death rate after CAS from 5.5% without the use of CPD to 1.8% with CPD. 4 Wholey et al, 22 on the global carotid artery stent registry, reported a reduction in stroke rate and procedure-related death from 5.29% in patients without protection to a 2.23% rate when using protection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,[17][18][19] Because of this relatively high incidence of adverse effects, efforts have been made to reduce their incidence by using CPDs during CAS. 4,5,20,21 An extensive literature review indicates that the use of CPD can decrease the incidence of 30-day combined stroke and death rate after CAS from 5.5% without the use of CPD to 1.8% with CPD. 4 Wholey et al, 22 on the global carotid artery stent registry, reported a reduction in stroke rate and procedure-related death from 5.29% in patients without protection to a 2.23% rate when using protection.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Nevertheless, one of the limitations of CAS is the potential for embolic stroke caused by plaque dislodgement of atheromatous material. 4,5 To prevent it, a variety of cerebral protection devices (CPDs) have been developed in the last years. Preliminary results have shown that these devices can significantly reduce thromboembolic complication during CAS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the past years, with the advent of CPDs, thromboembolic complications were significantly reduced. 7,8 Nevertheless, their clinical efficacy and safety are still a matter of controversy because they increase the risk of arterial vasospasm, thrombosis, and dissection. 9,10 Moreover, embolic signals have been observed by TCD during all phases of the carotid stent procedure, whereas in a recent study, more signals were detected with the use of filter devices.…”
mentioning
confidence: 99%
“…118,136 Ruptured plaque or thrombus identified with in-travascular sonography after stent evaluation may modify the decision to use intravenous heparin or glycoprotein IIB/IIIA inhibitors before the removal of the distal embolic protection device, ultimately reducing poststent embolic events. 13,118,[137][138][139][140][141][142][143] Intravascular sonography can also be potentially used during the treatment of an acute ischemic stroke to help identify the exact composition of the obstructing lesion-calcified versus fibrous versus soft clot. A more aggressive mechanical disruption/ retrieval strategy may be advocated in the presence of calcific or fibrotic occlusion.…”
Section: Future Utility Of Intravascular Sonographymentioning
confidence: 99%